(untitled) (Eurasian Scientific Herald, 2022)
In this article there is considered about innovative technologies in teaching finance terms in English lessons. When using a computer to control the quality of students’ knowledge, a greater objectivity of the assessment is also achieved. In addition, computer control can significantly save study time, as the knowledge of all students is checked simultaneously. This enables the teacher to pay more attention to the creative aspects of working with students.